Galápagos : imaginarios de la evolución textual en las islas encantadas - Mayorga, Esteban, 1977- (Purdue studies in Romance literatures, 2019)
"This book, written in Spanish, takes a literary and cultural studies model to explain the textual representation of the Galápagos Islands since their discovery until present day. The main argument suggests that the depiction of this crucial space for modernity in Western thought, given the rhetoric of travel and fiction writers, transforms the insular area with the intention of conceiving disparate forms of political displacement. Specifically, these depictions show several conflicts that arose from the seeking of identity in Ecuador during the nation-building project that took place at the time. As a result of colonial enterprises (scientific excursions, exile, tourism, journalistic pieces, expeditions, etc.), travel writings of the Galápagos condition the formation of the state and its national imagery because of the extreme symbolic capital of the archipelago and the desire of Latin American intellectuals to belong to a cosmopolitan territory"--